A Conserved Requirement for Fbxo7 During Male Germ Cell Cytoplasmic Remodeling - Rathje, Claudia C.; Randle, Suzanne J.; Al Rawi, Sara; Skinner, Benjamin M.; Nelson, David E.; Majumdar, Antara; Johnson, Emma E. P.; Bacon, Joanne; Vlazaki, Myrto; Affara, Nabeel A.; Ellis, Peter J.; Laman, Heike (Frontiers in Physiology, 2019)
Fbxo7 is the substrate-recognition subunit of an SCF-type ubiquitin E3 ligase complex. It has physiologically important functions in regulating mitophagy, proteasome activity and the cell cycle in multiple cell types, like neurons, lymphocytes and erythrocytes. Here we show that in addition to the previously-known Parkinsonian and haematopoietic phenotypes, Fbxo7-deficient male mice are completely sterile. In these males, despite successful meiosis, nuclear elongation and eviction of histones from chromatin, the developing spermatids are phagocytosed by Sertoli cells during late spermiogenesis, as the cells undergo cytoplasmic remodelling. Surprisingly, despite the loss of all germ cells, there was no evidence of the symplast formation and cell sloughing that is typically associated with spermatid death in other mouse sterility models, suggesting that novel cell death and/or cell disposal mechanisms may be engaged in Fbxo7-deficient males. Mutation of the Drosophila Fbxo7 orthologue, nutcracker (ntc) was previously shown to cause sterility at a similar stage of germ cell development, indicating that the requirement for Fbxo7 is conserved. The ntc phenotype was attributed to proteasome mis-regulation via an interaction with the proteasome regulator, DmPI31. Our data suggest rather that in mice, the requirement for Fbxo7 is either independent of its interaction with PI31, or relates specifically to cytoplasmic proteasome activity during spermiogenesis.